Correlating Shear Force and Coefficient of Friction to Platen Motor Current in Copper, Cobalt, and Shallow Trench Isolation Chemical Mechanical Planarization at Highly Non-Steady-State Conditions. (7th November 2019) - Frank, C.; Headley, R.; Sampurno, Y.; Philipossian, A.
Abstract : In this study we determined the relationships that exist between the coefficient of friction (COF) and platen motor current (PMC), and also between shear force and PMC at highly non-steady-state conditions during chemical mechanical planarization (CMP). For the 12 cases studied (8 for copper, and 4 for dielectric CMP including one as a cobalt buff step), we found that real-time PMC data closely mimicked shear force data as evident from high average values of correlation coefficient and coefficient of determination for all 12 cases (0.913 and 0.835, respectively). As for COF vs. PMC, average correlation coefficient and coefficient of determination for Cases A through D were 0.949 and 0.900, respectively. However, for the remaining 8 cases, correlation coefficients ranged from zero to 0.425, with coefficients of determination ranging from zero to 0.180. The reason behind the strong correlations seen in the first 4 cases, and the lack of any correlation seen in the remaining 8 cases, were explained based on the particulars of the dominant tribological mechanism for each case.